PERAN PONDOK PESANTREN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Zainuddin, Moh. Riza (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Boarding school as one of the sub-systems of education in Indonesia, has been instrumental in educating the nation and many of them gave birth to a leader who is able to counter the society, which is controversial in the religious and moral norms. The existence of a boarding school in addition to educational institutions as well as social institutions. Boarding school grow and develop together society since centuries ago, because it was the agency receives. Despite boarding implicitly connotes as traditional Islamic educational institutions, does not mean the whole boarding covered with innovation. In line with the demands of the changing times is the boarding school itself has been trying to find a new alternative to the road opening up, so it is not surprising that since a few years ago many good boarding schools who live in cities or in villages have been changing rapidly. Changes here known as renewal, not only concerning the financial matters but rather subtansional such as goals, systems, curriculum and so on.